Demokracja bezpośrednia a wprowadzenie praw wyborczych dla kobiet – przykład Szwajcarii - Musiał-Karg, Magdalena (Środkowoeuropejskie Studia Polityczne i Medioznawcze, 2012)
Over the centuries, Switzerland has developed a unique and inimitable statehood that functions in peculiar geographical, social and political conditions, shaped by the tradition of exercising direct forms of power. It appears, however, that these tools of direct democracy can sometimes obstruct the changes of utmost significance for the development of modern statehood and democracy. This was the case of granting voting rights to women. Although many European and other states granted the rights to vote and stand for election to women in the 1920s and 1930s, Switzerland needed much longer to introduce this change: on the federal level, women’s suffrage was granted as late as in 1971, and the last to enjoy the right to partake in the political life of their canton were the women of Appenzell Innerrhoden, granted the right in 1990. The objective of this paper is to analyze the influence of the mechanisms of direct democracy on the introduction of voting rights for Swiss women.